SARKOiDOZ HAST ALIGINDA ANTiFOSFOLiPiD ANTiKORLARININ ONEMi PRELiMiNER BiR ÇALIŞMA - SiPAHi, Sevtap; BİLİR, Muammer and ÖZBAKIR, Fatma and YANARDAĞ, Halil and ÇAĞATAY, Tülin (Cerrahpaşa Medical Journal, 2019)
Background and Design.- It is well-known that patients with sarcoidosis haw humeral immunologic abnormalities. Increases in serum immunglobulins and some autoantibodies as antinuclear antibody and rheumatoid factor haw been reported. In a wide variety of autoimmune and non-autoimmune disorders, occurance of antiphosholipid antibodies haw been detected. Our purpose was to evaluate the relationship between the occurence of antiphospholipid antibodies (APL-Ab) and sarcoidosis. lgG and lgM APL-Ab were estimated by enzyme linked immunoabsorbent assay (ELISA) in 26 untreated sarcoidosis patients (with a mean age of 45.2±16.8) whose diagnosis were established with histopathological and clinicoradiologic findings as well as 12 healthy controls (with a mean age of 45±15. 7). Results.- No significant correlation was obsen.ed between serum ALP-Ab lewl and sarcoidosis but only 4 of the 26 sarcoidosis patients who had skin lesions and eritema nodosum showed either pozitiw lgG or pozitiw lgM APL-Ab. Conclusion.- This preliminary study suggets that further studies are needed to assess the relationship between skin lesions and APL-Ab lewls in patients with sarcoidosis.